2002
DOI: 10.1016/s0022-5347(05)65245-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion Proteins As Tumor Suppressors

Abstract: Multiple and diverse cell adhesion molecules participate in intercellular and cell-extracellular matrix interactions of cancer. Cancer progression is a multistep process, in which some adhesion molecules have a pivotal role in the development of recurrent, invasive and distant metastasis. Recent data implicate some of these molecules in cell signaling and tumor suppression, which has important consequences for tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 85 publications
8
74
0
6
Order By: Relevance
“…Similar effects were obtained on human prostatic carcinoma cells, which showed increased Ecadherin (23)(24)(25) and prostate-specific antigen (26, 27) levels, but not on fibroblasts, hepatoma, kidney cancer, or leukemic cells. It is possible that this differential response to TDF is due to the presence or absence of TDF receptors.…”
Section: Discussionsupporting
confidence: 68%
“…Similar effects were obtained on human prostatic carcinoma cells, which showed increased Ecadherin (23)(24)(25) and prostate-specific antigen (26, 27) levels, but not on fibroblasts, hepatoma, kidney cancer, or leukemic cells. It is possible that this differential response to TDF is due to the presence or absence of TDF receptors.…”
Section: Discussionsupporting
confidence: 68%
“…During the last decade E-cadherin has increasingly been recognized as a potent tumour suppressor protein (Okegawa et al, 2002). Inactivation of the E-cadherin/ catenin adhesion complex usually correlates with poor prognosis and survival of cancer patients, most likely due to reinforced invasion and metastasis of tumour cells (Conacci-Sorrell et al, 2002;Cavallaro and Christofori, 2004).…”
Section: Deltaef1 and Cancer Progressionmentioning
confidence: 99%
“…The cadherin family includes N-, P-and E-cadherin (E-CAD) but only E-CAD is expressed in all epithelial tissues (1). E-CAD, a 120-kD glycoprotein located on chromosome 16 (3), is associated with intracellular proteins called catenins that mediate between extra-cellular signals and cytoskeleton microfilaments (4). The functions of E-CAD are related to tumor suppression and are generally down-regulated in epithelial tumor development and diffusion (5).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported that loss of E-CAD expression is associated with loss of cellular differentiation and increased cellular invasiveness (6). Moreover, E-CAD expression loss is related to high grade and advanced stage in many neoplasms, such as breast (7) and colorectal (8,9) cancers and urologic tumors (4,10). Recent studies have demonstrated that loss of normal E-CAD expression also correlates with poor prognosis in urothelial carcinoma (UC) of the upper urinary tract (11) and urinary bladder (5).…”
Section: Introductionmentioning
confidence: 99%